2012
DOI: 10.1155/2012/371714
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Pesticides in Natural Water: Effect of Hydrogen Peroxide

Abstract: The aim of this paper is to evaluate the effectiveness of photocatalytic treatment with titanium dioxide in the degradation of 44 organic pesticides analyzed systematically in the Ebro river basin (Spain). The effect of the addition of hydrogen peroxide in this treatment is studied, and a monitoring of effectiveness of photocatalytic processes is carried out by measurements of physical-chemical parameters of water. The application of photocatalytic treatment with 1 g L−1of TiO2during 30 minutes achieves an ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…Some authors have reported that the addition of hydrogen peroxide to photocatalytic treatment enhances the yield of the treatments, either through the inactivation of microorganisms [37,38] or through the removal of persistent organic micropollutants [39]. However, an excess of H 2 O 2 is detrimental to the final discolouration rate, and other studies confirm the results obtained from the TiO 2 /H 2 O 2 treatments performed in this research work.…”
Section: Comparison Of Processessupporting
confidence: 86%
“…Some authors have reported that the addition of hydrogen peroxide to photocatalytic treatment enhances the yield of the treatments, either through the inactivation of microorganisms [37,38] or through the removal of persistent organic micropollutants [39]. However, an excess of H 2 O 2 is detrimental to the final discolouration rate, and other studies confirm the results obtained from the TiO 2 /H 2 O 2 treatments performed in this research work.…”
Section: Comparison Of Processessupporting
confidence: 86%
“…The photocatalysis/H 2 O 2 treatment remains inferior to the photocatalytic treatment. In contrast, some authors have reported that the addition of hydrogen peroxide to photocatalytic treatment enhances the yield of the treatment, either in the inactivation of microorganisms or in the removal of organic persistent micropollutants . However, other studies confirm the results obtained in the photocatalysis and photocatalysis/H 2 O 2 treatments performed in this work.…”
Section: Resultssupporting
confidence: 51%
“…The Fenton reaction is frequently investigated as a physicochemical technology because it involves highly oxidative activity of hydroxyl radicals ( • OH) with respect to the substrates [1]. The • OH is the second most powerful oxidizing species after fluorine in aqueous media, and it is believed to destroy or even mineralize most organic substrates nonselectively in advanced oxidation processes [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%